Increasing youth voice in decision making through balancing power in school-based management committee in Nigeria - Umar, Bashiru Bako; Krauss, Steven Eric (2016)
Research has shown that youth voice in decision-making has the potentials to profit the youth themselves, the adults as well as the organization. However, most of the available research focuses on the outcome and not the process of youth voice in decision-making. In addition, the youth voice from Africa is “silent”, as limited research focusing on youth voice in decision-making comes from the continent. This paper is a qualitative study that employed multiple case study method to examine how youth voice in decision making is increased through youth-adult partnership in a school-based management committee. The findings show that developing mutual respect among members, developing new relationship between members, sharing responsibilities among members, providing adequate representation for youth, and building the capacity of members are crucial strategies for increasing youth voice in SBMC.